Characterization, Quality Assessment and Comparison of Selected Rice Landraces (Anadi, Bhotange, and Kalo Nuniya) of Nepal - Rai, Sakul; Khadka, Dambar Bd; Pokhrel, Bimala (Himalayan Journal of Science and Technology, 2023)
This study aimed to characterize, assess and compare the milling-, physical-, cooking-, and eating qualities of brown and milled rice landraces (Kalo Nuniya, Anadi, and Bhotange). Paddysamples ( 10 kg each) were cleaned, sun-dried to bring the moisture content to about 13-14%, shelled and then milled to obtain brown (unpolished) rice and milled (white/polished) rice, respectively. Milling-, physical-, cooking-, eating-, and nutritional properties of the rices were studied. The data generated were statistically analyzed using Genstat®version 12.1 for two-way ANOVA, and MS-Excel version 2019 for the Jarque-Bera test of homogeneity, correlation, and to generate graphical presentations. Bhotangehad better brown rice recovery (BRR=76.70%) and milled rice recovery (MRR=58.91%). Anadiand KaloNuniyahad poorer BRR (71.11%) and MRR (49.97%), respectively. Classifying rice samples based on the ‘grain type’, Anadi-, Bhotange-, and KaloNuniya-white were found to be of Medium-, Long-and Medium-’grain type’. Similarly, Anadi-, Bhotange-,and KaloNuniya-brown were found to be of Medium-, Medium-and Small-’grain type’, respectively. In terms of size (1000-kernel weight, TKW), Anadi, Bhotangeand KaloNuniya(all white/polished) were found to be ’Small’, ’Small’ and ’Tiny’. Equilibrium moisture content during soaking (EMC-S) negatively (moderate degree) correlated with apparent amylose content (AAC) for both milled-(R2=0.73) and brown rices (R2=0.70). In white-rices, apparent water uptake ratio (AWUR) showed moderate degree of positive correlation (R2=0.367) with length/breadth (l/b) ratio. But for brown rices, AWUR showed high degree of positive correlation (R2=0.793) with l/b ratio. Volume expansion ratio (VER) positively (moderate degree) correlated (R2=0.63) with AAC for milled rices. This simple correlation established between 2 parameters (assuming other factors to be the same) with few data points cannot be generalized and further investigations are needed to establish solid correlations. Both Bhotangewhite and Bhotangebrown, respectively, had better cooking properties with lower solid loss (both 1.36 ± 0.11%), cooking times (17.67±1.52 and 25.33±2.51 min), higher VER (2.78±0.03 and 2.70±0.04), and l/b ratios after cooking (3.03±0.03 and 2.59±0.03). Anadiwhite had a sticky texture shown by the least VER (2.63 ± 0.13) and the lowest AAC (15.70±1.03%). Classifying rice samples based on the ‘AAC’, Anadi-, Bhotange-,and KaloNuniya-white had Low-, Low-, and Intermediate AAC. Anadi-, Bhotange-, and KaloNuniya-brown had very Low-, Low-, and Low AAC, respectively. Classifying rice samples based on the GT, Anadi-, Bhotange-, and KaloNuniya-white had Low-, Low-, and Intermediate GT. Similarly, Anadi-, Bhotange-, and KaloNuniya-white had Intermediate-, High-, and High-GT, respectively.